Stool-based SDC2/SFRP2/TFPI2 methylation assay for colorectal neoplasia screening: a multicenter, case-control study - Li, Xiaoping; Liao, Qiuyu; Yang, Wenhui; Xiong, Zhiguo; Holmes, Mark; Li, Kaiyu; Pan, Jie; Yan, Jing; Liu, Gang (Frontiers in Oncology, 2026)
IntroductionColorectal neoplasia is a significant global health burden. Early detection is critical for improving clinical outcomes. However, developing a noninvasive strategy for routine detection of colorectal neoplasia remains challenging. This study evaluated the diagnostic performance of a combined SDC2/SFRP2/TFPI2 gene methylation stool DNA test for detecting colorectal cancer (CRC) and advanced adenoma (AA).MethodsA multicenter, case-control study was conducted involving 409 patients with CRC, 82 patients with AA, and 495 control participants between July 2022 and March 2024. Stool samples were collected from all participants and analyzed for SDC2, SFRP2, and TFPI2 methylation using quantitative fluorescent polymerase chain reaction (PCR). To evaluate the detection efficacy of the SDC2/SFRP2/TFPI2 methylation assay in comparison to conventional methods, fecal occult blood test (FOBT) and serum carcinoembryonic antigen (CEA) levels were measured in 110 CRC patients and 100 healthy individuals at Tianjin Medical University General Hospital.ResultsThe stool DNA test demonstrated high sensitivity for CRC (94.13%, 95% CI: 91.42-96.03) and AA (59.76%, 95% CI: 48.94-69.70), with 94.74% specificity (95% CI: 90.30-97.21) in the normal controls. Notably, the SDC2 marker displayed zero false positives among 98 digestive system cancer cases within the control groups, while SFRP2 and TFPI2 showed 8.16% and 10.2% false-positive rates, respectively. The stool DNA test accurately identified CRC, with an area under the receiver operating characteristic (ROC) curve (AUC) of 0.9343, and AA, with an AUC of 0.7729. Furthermore, positive stool DNA test results were significantly associated with distal cancer, ulcerative type, deeper tumor infiltration, flat-type AA, and lesions with high-grade dysplasia (P < 0.05). Among the 110 patients with CRC and 100 healthy controls, the AUC values for FOBT, CEA, and stool DNA were 0.7532, 0.6732, and 0.9399, respectively. The integration of all three detection methods achieved the highest detection efficacy (AUC = 0.9725).ConclusionThe combined methylation assay of SDC2, SFRP2, and TFPI2 outperformed FOBT and CEA in detecting CRC and AA, although further optimization is required for AA detection. Its high specificity and compatibility with routine screening procedures underscore its potential as a tool for detecting colorectal neoplasia.